2018
DOI: 10.1177/0961000618769980
|View full text |Cite
|
Sign up to set email alerts
|

Information discernment, mis-information and pro-active scepticism

Abstract: A participatory action research (PAR) approach was employed to investigate school students' information discernment capabilities. Placing school student participants at the centre of the research process enabled them to define the problem in their own words and begin to find solutions to the issue of how to choose good quality information. Findings confirmed the results of many studies that school students adopt a cognitive default position of trust and are relatively unquestioning when using information sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 30 publications
0
31
0
2
Order By: Relevance
“…Given these finding we argue that it is imperative that we attempt to enable all people to gain higher information discernment capabilities. Previous research (for example Walton and2013;Shenton and Pickard, 2014;Pickard, Shenton and Johnson, 2014;Walton and Cleland, 2017;Walton et al, 2018) has shown that this is achievable. The next section outlines a possible way of delivering effective information discernment teaching and learning.…”
Section: How Young People Make Judgements About Informationmentioning
confidence: 94%
See 3 more Smart Citations
“…Given these finding we argue that it is imperative that we attempt to enable all people to gain higher information discernment capabilities. Previous research (for example Walton and2013;Shenton and Pickard, 2014;Pickard, Shenton and Johnson, 2014;Walton and Cleland, 2017;Walton et al, 2018) has shown that this is achievable. The next section outlines a possible way of delivering effective information discernment teaching and learning.…”
Section: How Young People Make Judgements About Informationmentioning
confidence: 94%
“…It also leads them to use a wide variety of information to explore more than one side of an argument. We know from previous research that this cognitive questioning state can be operationalised in young people by employing the appropriate learning and teaching intervention (Walton and Hepworth, 2011;2013;Walton, 2017;Walton et al 2018). This is discussed more fully in the next section.…”
Section: How Young People Make Judgements About Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…This important factor is not an aspect examined in the ISCM. Through training, 16-17-year-old school students' initial lack of ID-who approached information in a trusting fashion; for example, using internet resources without regard to their provenance or quality (Walton, Pickard, & Dodd, 2018), could be enabled to adopt a cognitive questioning state, improving how they made judgments about the information they received (Walton & Hepworth, 2011). It is our contention that the ID framework presented in Figure 1.…”
Section: Why Information Science?mentioning
confidence: 99%